COMPARISON OF ATTENDED AND UNATTENDED CENTRAL AND PERIPHERAL OFFICE BLOOD PRESSURE MEASUREMENTS IN HYPERTENSIVE PATIENTS IN GENERAL PRACTICE. (April 2021) - Fuentes, Linda Elizabeth Villagomez; Höller, Julia; Riemer, Thomas Günther; Matthias, Klaus; Kreutz, Reinhold
Abstract : Objective: Central hemodynamic indices have been established as parameters of arterial health, but the prognostic value of central vs. conventional office blood pressure (OBP) measurements remains unclear. Furthermore, the use of attended vs. unattended automated OBP measurements is a current topic of controversy. Design and method: We conducted a prospective cohort study in general practice in Germany and included 42 consecutive patients with hypertension. The Mobil-O-Graph oscillometric device was used for the automated OBP recordings in all patients. Measurements were performed in a separate quiet room after five minutes rest in seated position. We compared in random order in each patient the attended vs. unattended automated central and peripheral systolic OBP (SOBP), diastolic OBP (DOBP), and pulse velocity wave (PVW). Results: The mean age of patients was 71 years (range 34–89 years, 54.8% females). Patients were treated on average with 1.95 antihypertensive drugs. The mean attended and unattended automated peripheral SOBP (131.7 and 131.6 mmHg, respectively) and DOBP (83.4 and 82.4 mmHg, respectively) values recorded by the device were not significantly different. In addition, there was no difference between the mean attended and unattended central aortic SOBP (120.1 and 120.2 mmHg, respectively) and DOBP (84.7 and 83.7 mmHg, respectively) values. Bland-Altman analysis revealed the small inter-individual differences between attended und unattended peripheral and central SOBP and DOBP values. There was no asymmetry and narrow limits of agreement between the two methods. Finally, no significant difference for PVW was found between attended and unattended measurements (10.1 and 10.2 m/sec, respectively). Conclusions: The attended versus unattended status of automated OBP measurements had no impact on derived peripheral OBP, central OBP and PVW values in general practice when using the Mobil-O-Graph oscillometric device.